Challenges in the treatment of fibrodysplasia ossificans progressiva - AKYÜZ, GÜLSEREN DERYA; YAĞCI, İLKER; DELİL, KENAN; ATA, PINAR (SPRINGER HEIDELBERG, 2019)
Fibrodysplasia ossificans progressiva (FOP), is a rare autosomal dominant connective tissue disease with a prevalence of 1 in 2 million. It is characterized by congenital foot deformities and multiple heterotopic ossifications in fibrous tissue. It usually starts with painful soft tissue swellings occurring with attacks at the ages of three or four. The attacks develop spontaneously or after minor trauma, and gradually turn into heterotopic ossifications that cause joint limitations, growth defects, skeletal deformities and chronic pain. The average life expectancy is forthy, and most of the patients are lost due to pulmonary complications. FOP is often misdiagnosed as fibromatosis, desmoid tumour or cancer, bunion, myositis, arthritis and rheumatic diseases. After clinical suspicion, confirmatory genetic analysis should be used for the diagnosis. The treatment of FOP is currently supportive. An effective, proven method has not yet been established. Herein, we present an 18-year-old female patient with FOP who underwent different treatment modalities in a 5-year period. This case-based review reveals all available treatment approaches with at least 6-month follow-up for FOP in the literature.
Keywords: Fibrodysplasia ossificans progressiva; Heterotopic ossification; Treatment; THERAPY; PATIENT